Carfilzomib-based combination regimens are highly effective frontline therapies for multiple myeloma and Waldenström's macroglobulinemia. Issue 4 (21st March 2019) - Chaudhry, Maria; Steiner, Raphael; Claussen, Catherine; Patel, Krina; Lee, Hans; Weber, Donna; Thomas, Sheeba; Feng, Chun; Amini, Behrang; Orlowski, Robert; Feng, Lei; Manasanch, Elisabet E.
Abstract: Multiple myeloma (MM) and Waldenström's macroglobulinemia (WM) are plasma cell disorders often treated with proteasome inhibitors. Recently, several studies evaluated carfilzomib as an initial treatment for these diseases and reported outstanding clinical outcomes. We conducted a retrospective study to report the efficacy and safety of frontline carfilzomib-based combinations in a standard of care setting. From 2014 until 2016 we identified newly diagnosed MM ( n  = 54) and WM ( n  = 6) patients treated with carfilzomib as initial therapy who met study inclusion criteria. The response rate for myeloma patients was 98% with 77% of patients undergoing upfront autologous stem cell transplant. The clinical benefit for WM was 100% with all patients having a resolution of B symptoms and anemia after treatment. Carfilzomib-based regimens are well tolerated and offer a neuropathy sparing approach with excellent responses both in newly diagnosed MM and WM making them a good choice for the frontline treatment of these diseases.